2005
DOI: 10.1149/1.1887166
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Spectroscopic Properties of Electrospun PAN-Based Fibrous Polymer Electrolytes

Abstract: Microporous fibrous polymer electrolytes were prepared by immersing electrospun poly͑acrylonitrile͒ ͑PAN͒-based fibrous membranes into lithium salt-based electrolytes. They showed high ionic conductivities of up to 1.0 ϫ 10 −3 S/cm at 20°C, and sufficient electrochemical stabilities of up to 4.5 V. Their ion conduction depended on the physicochemical properties of the lithium salt-based electrolytes trapped in pores, as well as on the interactions among the Li + ion, the carbonate, and the PAN. From the Fourie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(65 citation statements)
references
References 32 publications
2
63
0
Order By: Relevance
“…In addition, the variations in physical contact caused by the different separator morphology may also play a role in changing the electrochemical oxidation limit. These explanations are in agreement with earlier studies, which reported that electrolyte-soaked PAN fibrous membranes had improved electrochemical stability due to the high affinity of these membranes to the liquid electrolyte [27,28]. …”
Section: Electrochemical Oxidation Limitsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the variations in physical contact caused by the different separator morphology may also play a role in changing the electrochemical oxidation limit. These explanations are in agreement with earlier studies, which reported that electrolyte-soaked PAN fibrous membranes had improved electrochemical stability due to the high affinity of these membranes to the liquid electrolyte [27,28]. …”
Section: Electrochemical Oxidation Limitsupporting
confidence: 93%
“…Jung et al [26] reported increased electrochemical oxidation limit for PAN fibrous separators due to the good electrolyte absorption resulted from high specific surface area and thin fiber diameter. Raghavan et al [27] and Choi et al [28] also reported that the electrolyte-soaked fiber membranes with large surface area had improved electrochemical oxidation limit due to the formation of a large amount of complex compounds such as associated Li + -N≡C-group, associated Li + -O=C group, and associated C≡N-Li + -O=C group. Large and fully interconnected pores, high porosity, high specific surface area, uniform morphology were also reported as reasons of increased electrochemical oxidation limits when the average fiber diameter of fibrous separators decreased [27].…”
Section: Electrochemical Oxidation Limitmentioning
confidence: 99%
“…Recently, microporous polymer electrolytes composed of electrospun membranes made of PVdF, P(VdF-HFP) and PAN have been developed by Lee and co-workers [1][2][3][4]. These electrospun membranes are composed of ultrafine fibers with diameters in the range of tens of nanometers to several micrometers.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing interest in the electrospinning process of polymer solution or melt because of their several potent applications such as sensors, polymer electrolytes for lithium ion polymer battery, dye-sentized solar cell etc.. [10][11][12][13][14] Electrospinning is a powerful method of producing polymeric ultrafine fibers within the range of a few nanometers to a few hundred nanometers in diameter, which cannot be easily obtained using the traditional methods for making fibers. 15 Nano-sized fibers may be more helpful in obtaining carbon materials with well-defined pore structure compared to the carbonization of micro-sized polymer fibers.…”
Section: Introductionmentioning
confidence: 99%